Russian Federation, the World Trade Organization, and the Eurasian Customs Union : Tariff and Non-Tariff Policy Challenges - Ferrantino, Michael J.; Gillson, Ian; Schmidt, Gabriela (World Bank, Washington, DC, 2016)
This paper assesses issues relating to tariffs and nontariff measures (NTMs) in relation to Russia's World Trade Organization (WTO) and Eurasian Customs Union (ECU) commitments. The analysis finds that full implementation of Russia's WTO tariff schedule through 2020, would raise goods imports by about $3.5 billion (1.1 percent) compared to 2012, with estimates of welfare gains to Russian consumers equal to approximately $370 million. Russian exports to members of the ECU, primarily Kazakhstan, would increase by an estimated $194 million, measured against a 2008 baseline. The impact of NTMs in Russia and the ECU, though difficult to quantify, is potentially more important for the market than tariff changes, because of the significant divergence between the historical GOST standards and standards prevailing in most of Russia's trading partners. Formation of the ECU and its associated bodies in 2010 has tended to perpetuate regional methods of standard setting, and by extension NTM policies, that are closely aligned with older models.